PIDANA PENJARA DALAM PEMBAHARUAN HUKUM PIDANA INDONESIA - Kania, dede (Yustisia, 2014)
AbstractImprisonment as the main criminal is the most threatened against offenders. Imprisonment in Indonesia criminal law as a legacy of colonial law enforcement. With the development of the concept of criminal theory form retributive to restorative sentencing, imprisonment and the implementation should be reviewed so that can be in accordance with human rights principles. This research examined the imprisonment in the Indonesian criminal law, customary criminal law, and Islamic Penal law, and also the concept of imprisonment renewal in the concept of Criminal Law Code of Indonesia, and then what is the punishment that is accordance with restorative justice theory that can protect the human rights of the convicted person, victims, and society.Key Word: Imprisonment, human rights, restorative justice.AbstrakPidana penjara sebagai pidana pokok merupakan pidana yang paling banyak diancamkan terhadap pelaku kejahatan. Pemberlakuannya merupakan peninggalan hukum kolonial. Dengan perkembangan pemikiran mengenai konsep pemidanaan dari retributif ke restoratif, pelaksanaan pidana penjara pun harus dikaji ulang sehingga dalam penjatuhan maupun pelaksanaannya dapat sesuai dengan prinsip hak asasi manusia. Penelitian ini mengkaji penerapan pidana penjara dalam hukum pidana Indonesia, hukum pidana adat, dan hukum pidana Islam, serta konsep pembaharuan pidana penjara dalam RKUHP, kemudian bentuk pembaharuan pemidanaan apakah yang sesuai dengan teori restorative justice yang dapat melindungi hak asasi terpidana, korban, dan masyarakat.Kata Kunci: Pidana penjara, hak asasi manusia, keadilan restoratif